Nabi dan Mukjizat - Kustono, Antonius Hari (Jurnal Orientasi Baru, 2013)
Three key terms are used of the prophet: roâ€™eh, hozeh, nabi. The terms roâ€™eh and hozeh are translated as â€œseerâ€, while the most important term is nabi, which is usually translated â€œprophet.â€ It means â€œone who is called to speak.â€ There is no particular reference to the prophets as â€œmen of miracleâ€ in the Old Testament. However, we have two prophets, Elijah and Elisha, who performed amazing and powerful miracles of the Lord. Within about sixtyfive years after Solomonâ€™s death the nation of Israel had reverted back to such a state of apostasy from God that the prophet Elijah was raised up to witness against them. He was succeeded by Elisha who asked for a double portion of Elijahâ€™s miraculous powers (2 Kings 2:9). Both men prophesied in one of Israelâ€™s greatest times of disloyalty to God. Through their stories and miracles we are reminded to the Hebrew word â€œdabarâ€ which is sometimes used in reference to the â€œDivine Wordâ€ and also in an active sense as the â€œDivine Workâ€.